Variability in Fruit Production of Carapa Guianensis Associated with Edaphoclimatic Factors in the Amazon - Angulo Villacorta, Carlos Darwin; Silva da Conceição, Denilson; Chuchon Remon, Rodolfo Juan; Manigat, Donald; Antunez Jimenez, Lorena; de Toledo, José Julio (Preprints.org (MDPI), 2026)
Carapa guianensis Aubl., widely distributed throughout the Amazon, is recognized for its ecological, economic, and social importance, and constitutes a key source of income for numerous extractive communities. However, fruit production exhibits marked spatial variation that may be influenced by soil properties and climatic factors. In this study, we assessed this variability using data from 21 studies conducted in the Brazilian Amazon, incorporating georeferenced information from each site on climate and soil characteristics. Environmental variables were evaluated using Random Forest models. Average fruit productivity showed a broad range (0.34 to 34.6 kg·tree⁻¹·year⁻¹), with higher values in várzea forests (16.5 kg·tree⁻¹·year⁻¹) and lower values in igapó forests (2.5 kg·tree⁻¹·year⁻¹). The model explained 42% of the observed variability (R² = 0.83 in cross-validation), identifying soil organic carbon, mean annual temperature, and clay content as the most influential predictors. These findings demonstrate that fruit production is shaped by the interaction between edaphic and climatic conditions, which determine the species' productivity patterns, and highlight the need to foster adaptive management strategies that ensure the sustainable use of andiroba across Amazonian ecosystems.